2021
DOI: 10.3390/machines9120332
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Root Canal Preparation with ProTaper Next, WaveOne Gold, and Twisted Files on Dentine Crack Formation

Abstract: (1) Background: Root canal preparation constitutes an important factor for success in endodontics. However, various complications may occur during this stage. The aim of this study was to compare the incidence of cracks within radicular dentin after instrumentation with ProTaper Next (PTN), WaveOne Gold (WOG), and Twisted Files (TF), which utilize different kinematics. (2) Methods: Eighty single-rooted teeth were classified into four groups (n = 20). Three groups were instrumented using PTN (X1, X2), WOG (Prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Of these 171 articles, 73 were discarded because they evaluated endodontic instrument fracture, while 14 were not included as they studied fracture resistance using different root-canal cements; 12 were discarded since they analyzed the ability to clean an endodontic space shaped with a different taper, while 52 were discarded because they were not related to the review’s objectives. In all, 20 studies were included in this review [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] ( Figure 1 ). The included papers are listed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 171 articles, 73 were discarded because they evaluated endodontic instrument fracture, while 14 were not included as they studied fracture resistance using different root-canal cements; 12 were discarded since they analyzed the ability to clean an endodontic space shaped with a different taper, while 52 were discarded because they were not related to the review’s objectives. In all, 20 studies were included in this review [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] ( Figure 1 ). The included papers are listed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In fact, these defects can be observed in extracted and stored teeth and may be due to procedural errors in the preparation of the experimental samples, rather than merely being due to the shaping [ 54 ]. Moreover, the studies that analyze microcrack formation showed discordant results, even when compared to each other [ 28 , 34 , 39 , 40 , 41 , 42 , 44 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%